2014
DOI: 10.52638/rfpt.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Télédétection, SIG et modélisation de l'érosion hydrique dans le bassin versant de l'oued Amzaz, Rif Central

Abstract: Le bassin versant de l'oued Amzaz (Maroc, Rif central) est caractérisé par un climat semi-aride. Des pluies irrégulières, le plus souvent à caractère orageux combinées à une déforestation importante provoquent une érosion sévère. Les sols sont de plus en plus dégradés et les sédiments issus de cette érosion contribuent à l'envasement des retenues de barrages. L'intégration des cartes thématiques des différents facteurs de l'Equation de Gavrilovic (EPM) dans le Système d'Information Géographique (SIG) avec leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The slope of the terrain affects erosion by its degree of inclination. This has been demonstrated by several studies [62][63][64][65][66][67]. An increase in slope enhances run-off, which becomes erosion-prone, and its energy surpasses that of raindrops [1,68].…”
mentioning
confidence: 82%
“…The slope of the terrain affects erosion by its degree of inclination. This has been demonstrated by several studies [62][63][64][65][66][67]. An increase in slope enhances run-off, which becomes erosion-prone, and its energy surpasses that of raindrops [1,68].…”
mentioning
confidence: 82%
“…The production of the map ("H" factor) of rainfall in the Admer-Ezem watershed is also based on data from the Agence du Bassin Hydraulique l'oum-Erabaa (ABHB). The isohyet map, shown in Figure (8), was created using the Thiessen approach, which takes into account the possibility of a precipitation gradient between the various stations within the research region. The highest values are recorded in the western and northern part of the basin (Ouiouane station and Ain kahla station) pouring, while the lowest values occur at the Senoual station, which is directly related to the change elevation and orientation of slopes.…”
Section: Annual Precipitation Average (H)mentioning
confidence: 99%
“…It has also been applied in Morocco in the central Rif [Chaaouan, 2015;Hmamouchi, 2018], central Middle Atlas [Limame,2021, Lakhili et al, 2021 western Rif [ Zahnoun et al, 2020] Toudgha River watershed of the central hight Atlas [Elbadaoui et al,2023], the majority of these studies concluded that the EPM model was the closest to reality compared to the other models.…”
Section: Introductionmentioning
confidence: 99%
“…The X a value ranges from 0.05 for areas with dense vegetation to 1.0 for bare soil [SAKUNO et al 2020]. To determine the X a coefficient, we followed the methodology proposed by ZORN and KOMAC [2008], where X a was estimated by the use of a modified NDVI (X a NDVI) [CHAAOUAN et al 2013], using equations shown in Table 3.…”
Section: Soil Protection Coefficient (X a )mentioning
confidence: 99%
“…It is followed by sedimentation in steep areas, reservoirs, irrigation systems and waterways [CERDÀ, DOERR 2008;EFTHIMIOU et al 2016;KUNTA 2009]. Soil erosion is mainly caused by rain splash impact (separation), while rill and gully erosion are caused by flowing water (separation, transport) [CHAAOUAN et al 2013;EFTHIMIOU et al 2017;HAAN et al 1994].…”
Section: Introductionmentioning
confidence: 99%